(untitled) (Journal of Human Sciences, 2018)
This research presents a wonderful experience of the Libyan people during the stage of its struggle against the Italian invasion in the period (1918 - 1922), where the leaders of the Jihad gathered in the mosque Almjabra in the region of Amslata on November 16, 1918 and announced the formation of the Republic of Tripoli as a political system in the western region of Libya. The Presidential Council issued several resolutions and letters addressed to Western countries in order to recognize this republic, and at the top of these countries was Italy, which refused to recognize this new entity and entered with the Mujahideen In Asht The armed Mujahideen in which the Mujahideen revealed their strength against the Italian forces, which led them to sit with them at the negotiating table in Khalat al-Zaytouna. They failed it. During these few years, the republic was subjected to many attempts to thwart it by the Italian authorities, from the policy of procrastination not to recognize it to the policy of divide and rule and support the parties to the arms, and finally the military operations that ended with the occupation of Italian forces throughout the western region and ended the Republic of Tripoli.